Antibacterial activity of alcohol extract of Quercusinfectoria Olivier - Rajaa A. Hussein; Huda A. Salih; Inas R. Mehdi (Al-Qadisiyah Journal of Pure Science, 2018)
Eighteen clinical ear and wound swaps were collected from patients attending AlfuratAl-awsatHospital in Al-KufaCity , bacterial isolates were identified after culturing the swaps , the results indicated that the most frequent isolates were Pseudomonas aeuroginosa and Acinobacter baumanii. Extract from Quercusinfectoria was prepared using ethyl alcohol as a high polarity solvent then screened for antibacterial activity at the concentrations(125,250,375, and 500mg/ml) using agar well diffusion method. Crud extract exhibited a strong inhibition effect against P. aeruginosa ranging between (13.5-22.5mm) and moderate antibacterial effect for A. baumanii (13-18mm).